Are the traffic lights red? Perspectives on stage lighting during the pandemic and strategies used for remote theater (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2021)
This article seeks to discuss perspectives on stage lighting during the covid-19 pandemic and the possible strategies used in its conception and execution. Based on the concept of cyberculture, developed by Pierre Lévy, we sought to discuss the relationship between theater and new means of consumption based on the use of technologies and virtualities, with an emphasis on the work of the lighting designer. For this, the elaboration and execution of the lighting project of three spectacle performed during the pandemic in 2020 and 2021 were analyzed, which are: Crave, Thoughts On Peace In An Air Raid and The tiger. It was observed in the analysis of the processes which strategies were used according to the conditions imposed by the pandemic. After the analysis, it was possible to conclude that despite different means and equipment, what prevails in the elaboration of lighting is the concept of light-language and what you wants to communicate.
Keywords: stage lighting; pandemic; remote theater; cyberculture; light-language